AKTIVITAS EKSTRAK DAUN SIRSAK (Annona muricata L.) SECARA IN VIVO TERHADAP SCABIES PADA KAMBING KACANG (Capra hircus). - Risyani, Risna; Jamaluddin, Abdul Wahid; Mursalim, Muhammad Fadhlullah (Jurnal Ilmiah As-Syifaa, 2018)
The research was purposed to determine the activity of the leaf extract of soursop (Annona muricata L.) in dealing with scabies on Indonesian Native Kacang Goat (Capra hircus). There were 25 samples of scabies wounds used in this research. The samples were selected by examining the skin scrapings microscopically on goat which showed clinical symptoms of scabies to ensure mite infestion, Sarcoptes scabiei. Goat scabies are grouped into five treatment groups which consist of the positive control group, the negative control group, the group which was given the extract of soursop leaf of 10% concentration, the group which was given the extract of soursop leaf 20% concentration, and the group which was given the extract of soursop leaf extract 30% concentration. The treatment was given every day for seven days. The observation and the success assessment of scabies healing using a scoring method based on parameters of skin clinical changes consist of hair growth, scab, thickening, and skin folds. The conclusion of this research is the soursop leaf extract has an activity in healing scabies on Indonesian Native Kacang Goat (Capra hircus).Â